Comparative Study on Relative Fossil Energy Carrying Capacity in China and the United States - Zhili Zuo; Jinhua Cheng; Haixiang Guo; Yonglin Li (Energies, 2021)
Based on resource carrying capacity, this study used the revised theory of relative resource carrying capacity (RRCC) and introduced an innovative concept of relative fossil energy carrying capacity (RFECC), which evaluates the degree of fossil energy sustainability based on the relationship between economy, population, and environment. This study took China and the United States as the study objects, took the whole country as the reference area, and calculated the RFECC of population, economic, and environmental resources from 2000 to 2018. Therefore, based on the comparative analysis, the following conclusions were drawn: (i) there is a big difference in the RFECC between China and the United States, which is manifested in the inverted U-shaped trend in China and the U-shaped trend in the United States; (ii) the relative fossil energy carrying states in China and the United States are different, mainly reflected in the economy and environment; (iii) the gap in RFECC between China and the United States has gradually widened; in general, China’s economic RFECC is better than that of the United States, while environmental RFECC and population RFECC in the United States is better than that of China; and (iv) coal and oil should be used as a breakthrough point for the sustainable fossil energy and sustainable development for China and the United States, respectively.